Airborne anaphylaxis: highlighting an invisible enemy. Issue 5 (4th October 2022) - Ridolo, Erminia; Incorvaia, Cristoforo; Schroeder, Jan Walter
Abstract : Purpose of review: Airborne anaphylaxis is a rare disorder defined by the occurrence of anaphylactic reactions to inhaled allergens, which may arise not only in occupational exposure but also in common settings. Foods are the most common cause of airborne anaphylaxis, even organic mixtures scents. The other important cause is represented by drugs, while in the wide range of other causes, there are often reports on unique cases. This review aims to make an overview about the potential causes of airborne anaphylaxis, by analysing what is described in literature on this topic. Recent findings: Concerning epidemiology, no data on specific prevalence of airborne allergy in adults are available. To date, only one study evaluated the specific prevalence of airborne allergy with anaphylaxis to foods in children, resulting in 5.9% of reactions due to exposure to aerosolized foods, compared with 78% of reactions caused by food ingestion. In addition to anaphylaxis, airborne-related reactions may also present with symptoms such as rhino-conjunctivitis, wheezing, dyspnoea and asthma. Summary: A detailed anamnesis facilitates a correct diagnosis, which allows appropriate therapeutic and preventive interventions, but, similarly to rare diseases in general, only specialized doctors are able to implement it. The assumption of the approach used in emergency medicine for other causes of anaphylaxis, that is referring the patient at discharge to an allergist who will teach the basic notions to recognize symptoms and access the appropriate therapy, would allow the patient to avoid situations of serious danger.